A study of gamma-ray and neutron radiation in the interaction of a 2 MeV proton beam with various materials. (December 2015) - Kasatov, D.; Makarov, A.; Shchudlo, I.; Taskaev, S.
Abstract: Epithermal neutron source based on a tandem accelerator with vacuum insulation and lithium target has been proposed, developed and operated in Budker Institute of Nuclear Physics. The source is regarded as a prototype of a future compact device suitable for carrying out BNCT in oncology centers. In this work the measurements of gamma-ray and neutron radiation are presented for the interaction of a 2 MeV proton beam with various materials (Li, C, F, Al, V, Ti, Cu, Mo, stainless steel, and Ta). The obtained results enabled the optimization of the neutron-generating target and the high energy beam transportation path. Highlights: Radiation is measured for interaction of 2 MeV protons with various materials. Absorption of protons in molybdenum and tantalum leads to minimal radiation. Neutron generating target with thin lithium layer for BNCT must be made of tantalum.